The principles of PK-tailored prophylaxis - Reininger, A. J.; Chehadeh, H. E. (Hämostaseologie, 2013)
While prophylaxis with factor VIII (FVIII) is considered the first choice therapy for patients with severe haemophilia A the optimal prophylaxis regimen is still under scientific debate. A recent study demonstrated efficacy and safety of a PK-tailored prophylaxis regimen with rFVIII (ADVATE) aimed to maintain FVIII trough levels of ≥1% (19). The annual bleed rate (ABR) could be significantly reduced compared to the previous on-demand treatment period (p < 0.0001) and bodily pain, a health-related quality of life dimension of the SF-36v1 questionnaire also significantly improved (p = 0.0007). Thus PKtailored prophylaxis with ADVATE might offer a valid alternative to standard prophylaxis. Open issues to be considered for implementation of PK-tailored prophylaxis are: What FVIII trough level is needed to prevent any bleed? Do patients with target joints need higher FVIII trough levels to stay bleed-free? Are there user-friendly tools available to calculate individualized PK-driven prophylaxis doses and frequency without the need for a full 9-sample PK curve?Current knowledge on these aspects as well as some considerations about the future of PK-tailored prophylaxis is discussed.
Keywords: Haemophilia A; PK tailored prophylaxis; annual bleed rate; ABR; individualized treatment; FVIII trough level; target joint